KAJIAN FILOSOFI AQIQAH DAN UDHIYAH (PERSPEKIF ALQUR'AN DAN SUNNAH) - Hj. Nurnaningsih, Hj. Nurnaningsih (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
Aqiqah and Udhiyah which is a keyword in this paper are described by a system of philosophy, using descriptive qualitative method that aims to provide an understanding of all aspects related to the need for its implementation Syar’i and the conditions specified in the legal basis for al qur'an, Sunnah and ijma 'Ulama. There are several views about the need for the implementation of Aqiqah and Udhiyah so that in principle it can be said is a guidance Worship categorized in